The Mixed Blessing of Leader Sense of Humor: Examining Costs and Benefits - Yam, Kai Chi; Christian, Michael S.; Wei, Wu; Liao, Zhenyu; Nai, Jared (Academy of Management Journal, 2018)
Workplace humor is ubiquitous, yet scholars know little about how it affects employees’ behaviors in organizations. We draw on an emerging psychological theory of humor—benign violation theory—to suggest that a leader’s sense of humor often conveys counter-normative social information in organizations. We integrate this theory with social information processing theory to develop hypotheses about the effects of a leader’s sense of humor on follower behavior. We suggest that although a leader’s sense of humor is positively associated with leader−member exchange and ultimately work engagement, it can also signal to followers the acceptability of norm violation at work. These perceptions in turn are positively associated with followers’ deviance. Furthermore, we propose that these indirect effects are moderated by leader aggressive humor. Data from two three-wave field studies in China and the United States provide support for our hypotheses. Taken together, our results suggest that a leader’s sense of humor can be a mixed blessing and elicit unforeseen negative behaviors from their followers.